2017
DOI: 10.1007/s11104-017-3336-4
|View full text |Cite
|
Sign up to set email alerts
|

An improved formula for evaluating electrical capacitance using the dissipation factor

Abstract: 16Background and aims The measurement of electrical capacitance in root-soil system (C R ) is a useful method for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…1) demonstrate that the capacitance detected was a reliable predictor of root system size for various species and growing media. The large differences in the regression parameters were consistent with previous observations (Beem et al, 1998;Aulen and Shipley, 2012;Cseresnyés et al, 2017), and showed the relative nature of C RSS measurement. The regression fit (R 2 ) decreased with increasing substrate complexity (pumice < arenosol < chernozem) due to the dielectric behaviour of the variably charged soil colloids, including clay minerals and organic materials (Hilhorst, 1998), which cause interference with the plant response (Ozier-Lafontaine and Bajazet, 2005;Postic and Doussan, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1) demonstrate that the capacitance detected was a reliable predictor of root system size for various species and growing media. The large differences in the regression parameters were consistent with previous observations (Beem et al, 1998;Aulen and Shipley, 2012;Cseresnyés et al, 2017), and showed the relative nature of C RSS measurement. The regression fit (R 2 ) decreased with increasing substrate complexity (pumice < arenosol < chernozem) due to the dielectric behaviour of the variably charged soil colloids, including clay minerals and organic materials (Hilhorst, 1998), which cause interference with the plant response (Ozier-Lafontaine and Bajazet, 2005;Postic and Doussan, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…the reciprocal of the effective capacitance is the sum of the reciprocal of individual capacitances), if the soil capacitance (C Soil ) is much higher than the root capacitance (C Root ), C RSS is determined by the root system (Rajkai et al, 2005;Dietrich et al, 2013). A subsequent study provided experimental support for the concept of TCM (Kormanek et al, 2016), and the high capacitances detected for various types of substrates at field capacity also meet the model's criteria (Dietrich et al, 2013;Ellis et al, 2013;Cseresnyés et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The other reason for the decrease in electrical capacitance is that lignin and suberin have a lower permittivity than the other main component materials of the root. The variability in their quantity causes a considerable variation in the dielectric properties of the root tissue (Cseresnyés et al, 2017). A root system with young active roots therefore has a greater capacitance.…”
Section: Theorymentioning
confidence: 99%
“…Therefore, the differences between the function parameters were attributed to the thick taproot of the species, specifically to the weak allometry between taproot traits, derived from the relatively high root weight to surface area (Cseresnyés et al 2017;Wu et al 2017), and thus were ignored in further analysis.…”
Section: Pilot Experimentsmentioning
confidence: 99%